Knowledge Level of Farmers on Sugarcane Production Technology in Badaun District of Uttar Pradesh - Chauhan, Rajeev Singh; Kumar, Rupendra; Mishra, Yagya Dev; kumar, Punit; Singh, J.P. (Indian Journal of Extension Education, 2018)
Sugarcane is one of the major crops of Uttar Pradesh. But, sugarcane productivity of Uttar Pradesh remained very low as compared to southern states, which may be due to lack of farmers’ knowledge and its practice about recommended sugarcane production technologies. Keeping this in view, present study was conducted in Asafpur block of Badaun district in Bareilly division of Uttar Pradesh. A randomly selected sample of 250 sugarcane growing farmers was interviewed with the help of an interview schedule. It was found that majority of large and medium farmers possessed good knowledge regarding soil, seed, fertilizer and irrigation technologies of sugarcane crop while it is reverse in case of small farmers.
Keywords: Knowledge level; sugarcane production technology